2023
DOI: 10.3390/ijerph20065158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Rapid Weight Loss Strategies and Percentages on Performance-Related Parameters in Combat Sports: An Updated Systematic Review

Abstract: Most combat sports (CS) are structured in weight categories, and it is very common to carry out body weight adjustment strategies in order to compete in lower weight categories. For this reason, different rapid weight loss (RWL) strategies are usually performed to pass the pre-competition weigh-in test, and then a replenishment of fluids and carbohydrate-rich foods is conducted in an attempt to recover the weight and avoid a performance loss. In this context, no clear references have been found on whether thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
4
0
2
Order By: Relevance
“…Therefore, athletes need to gain more advantages (e.g., height, arm span, strength) through WL to increase their possibility of winning competitions. While losing weight may not lead to intrinsic performance improvements [56][57][58][59] or a higher probability of winning [60][61][62], they believe it will lead to an advantage [63].…”
Section: Prevalence Of Wlmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, athletes need to gain more advantages (e.g., height, arm span, strength) through WL to increase their possibility of winning competitions. While losing weight may not lead to intrinsic performance improvements [56][57][58][59] or a higher probability of winning [60][61][62], they believe it will lead to an advantage [63].…”
Section: Prevalence Of Wlmentioning
confidence: 99%
“…Except for the studies of Sambo, MMA, and Muay Thai athletes, all studies reported that the athletes' habitual WL was less than 5%, which is in line with the above research recommendations. Although previous studies addressing the effects of RWL on physiological parameters have produced conflicting data, demonstrating negative [69][70][71], positive [72], and negligible [72,73] effects, some systematic reviews and meta-analyses have shown no or negative effects of RWL on athletic performance [56][57][58]74].…”
Section: Weight Historymentioning
confidence: 99%
“…Neste sentido, o estudo de Aranda et al (2023), uma revisão sistemática da literatura que objetivou trazer os efeitos que as diferentes estratégias de perda de peso poderiam trazer na saúde e performance do atleta, utilizou um total de 16 estudos, totalizando uma amostra de 184 atletas, sendo estes com pelo menos três anos de prática em esportes de combate e também uma experiência prévia em perda de peso rápida.…”
Section: Relações Da Hidratação No Período Pré E Pós Competições Em A...unclassified
“…Obteve como resultado que a perda de peso entre 3 -5% da massa corporal total do atleta seria o ideal para a performance física e psicológica, trazendo ainda que se esta perda for gradual e o período de recuperação entre pesagem e luta for de >24h, seria menos prejudicial a saúde do atleta, pois o mesmo conseguiria atingir o peso e hidratar sem grandes intercorrência e sem prejuízos na capacidade física e funcional (Aranda et al, 2023).…”
Section: Relações Da Hidratação No Período Pré E Pós Competições Em A...unclassified
“…Moreover, in combat sports, the reaction times and hit accuracy rates of competitors who chose to lose more than 5% of their body body mass were negatively affected [ 10 ]. Therefore, it seems to be a better choice at this stage to lose body mass gradually over a few weeks in competitions or qualifiers that last a few days [ 11 ]. In the case of boxers, this has not been investigated in depth.…”
Section: Introductionmentioning
confidence: 99%